Non-communicable diseases in Mozambique: risk factors, burden, response and outcomes to date - Silva-Matos Carla; Beran David (BMC, 2012)
Abstract Mozambique is located on the East Coast of Africa bordering South Africa, Zimbabwe, Zambia, Malawi and Tanzania and is one of the poorest countries in the world. Currently NCDs account for 28% of deaths in Mozambique. Risk factors such as tobacco and alcohol use and poor diet are present in both urban and rural settings. Diseases such as hypertension and diabetes affect large proportions of the population, but people are often unaware of their condition or poorly managed. Data from studies on diabetes highlight the financial burden for NCD management in Mozambique for both the individual and health system. The National Strategic Plan for the prevention and control of NCDs in Mozambique has as its aim to create a positive environment to minimise or eliminate the exposure to risk factors and guarantee access to care. The plan has as its overall objective to reduce exposure to risk factors and morbidity and mortality due to NCDs and has 4 areas of intervention: 1) Prevention and health education with regards to NCDs; 2) Access to quality care, treatment and follow-up; 3) Prevention of disability and premature mortality and 4) Surveillance, research, monitoring and evaluation and advocacy for NCDs. The Ministry of Health developed projects for diabetes and hypertension and used these as key lessons that could then be applied to other NCDs. Mozambique, through political commitment from the Ministry of Health and the dedication of local champions, has been able to garner international support to improve care for people with diabetes and then use this to develop its National Plan for NCDs. Despite this increase in attention resources available do not match the challenge of NCDs in Mozambique. Mozambique's experience provides a practical example of actions that can be undertaken in a resource poor country to tackle the emerging burden of NCDs.